LONP1 targets HMGCS2 to protect mitochondrial function and attenuate chronic kidney disease. Issue 2 (11th January 2023) - Bai, Mi; Wu, Mengqiu; Jiang, Mingzhu; He, Jia; Deng, Xu; Xu, Shuang; Fan, Jiaojiao; Miao, Mengqiu; Wang, Ting; Li, Yuting; Yu, Xiaowen; Wang, Lin; et al.
Abstract: Mitochondria comprise the central metabolic hub of cells and their imbalance plays a pathogenic role in chronic kidney disease (CKD). Here, we studied Lon protease 1 (LONP1), a major mitochondrial protease, as its role in CKD pathogenesis is unclear. LONP1 expression was decreased in human patients and mice with CKD, and tubular‐specific Lonp1 overexpression mitigated renal injury and mitochondrial dysfunction in two different models of CKD, but these outcomes were aggravated by Lonp1 deletion. These results were confirmed in renal tubular epithelial cells in vitro . Mechanistically, LONP1 downregulation caused mitochondrial accumulation of the LONP1 substrate, 3‐hydroxy‐3‐methylglutaryl‐CoA synthase 2 (HMGCS2), which disrupted mitochondrial function and further accelerated CKD progression. Finally, computer‐aided virtual screening was performed, which identified a novel LONP1 activator. Pharmacologically, the LONP1 activator attenuated renal fibrosis and mitochondrial dysfunction. Collectively, these results imply that LONP1 is a promising therapeutic target for treating CKD. Synopsis: Activation of the mitochondrial protease Lon protease 1 (LONP1) attenuates mitochondrial dysfunction and renal fibrosis in chronic kidney disease (CKD) mice, suggesting that targeting LONP1 might represent a novel therapeutic strategy for CKD. CKD patients and mice have decreased LONP1 expression. The substrate of LONP1, HMGCS2, accumulates in mitochondria causing mitochondrial dysfunction and accelerating CKD progression. Activation of LONP1 by the newly identified activator 84‐B10 improves mitochondrial function and reduces renal fibrosis in CKD mouse model. Abstract : Activation of the mitochondrial protease Lon protease 1 (LONP1) attenuates mitochondrial dysfunction and renal fibrosis in chronic kidney disease (CKD) mice, suggesting that targeting LONP1 might represent a novel therapeutic strategy for CKD.